2011
DOI: 10.3109/02656736.2011.595380
|View full text |Cite
|
Sign up to set email alerts
|

In vivo wound healing and dermal matrix remodelling in response to fractional CO2 laser intervention: Clinicopathological correlation in non-facial skin

Abstract: With the above-mentioned low and medium parameter settings, ablative fractional photothermolysis is safe and effective in non-facial skin. However, dermal remodelling continues for up to 4 weeks, which should be the minimum space between treatment sessions. Higher energies may induce granuloma formation, possibly a sign of an overstrained remodelling capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 20 publications
6
38
0
2
Order By: Relevance
“…We found that laser channels remained open during the first 24 hours, which may raise perspectives for optimal timing of laser‐assisted drug delivery. Majority of AFXL‐channels appeared closed from day 2 onwards, which is in accordance with both previous histological assessments and previous RCM‐studies, suggesting initial re‐epithelialization to take place within 2–3 days .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that laser channels remained open during the first 24 hours, which may raise perspectives for optimal timing of laser‐assisted drug delivery. Majority of AFXL‐channels appeared closed from day 2 onwards, which is in accordance with both previous histological assessments and previous RCM‐studies, suggesting initial re‐epithelialization to take place within 2–3 days .…”
Section: Discussionsupporting
confidence: 91%
“…AFXL induces “microscopic ablation zones” (MAZs) characterized by vertical centrally ablated channels, extending into epidermal and dermal compartments, depending on the pulse energies used. The central ablation defect is surrounded by a necrotic eschar, which is further surrounded by a zone of thermally denatured collagen . A crust of microscopic epidermal necrotic debris (MEND) covers the ablation defect.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, our finding suggests show that wound recovery starts from the deeper tissue, which is also consistent with previous reports [38]. As compared with the previous report [39], it indicates that the wounds can completely heal in two weeks after AFL exposures. In the stark contrast, the epidermis has already reepithelialized with partial restoration of the basement membrane after 72 hours of NAFL treatment.…”
Section: Quantitative Analysis and Discussionsupporting
confidence: 82%
“…10 However, unprecedented treatment depths (up to 4 mm with current devices) combined with tissue sparing adjacent to ablative columns probably facilitates rapid reepithelialization and provides ample viable cells to drive a vigorous remodeling response while maintaining excellent safety margins. [11][12][13][14][15] Gains in ROM observed in the immediate postoperative period probably derive from photomechanical fenestration of stiff scar tissue. Long-term, persistent gains in function and improvements in scar characteristics probably result from gradual diffuse dermal remodeling and a relative normalization of dysfunctional scar tissue.…”
Section: Discussionmentioning
confidence: 99%